Analisis Gaya Mengajar Guru IPA Terhadap Motivasi Belajar Peserta Didik kelas VII SMP Katolik Adisucipto Penfui Nusa Tenggara Timur - Gabriel Sawu; Hildegardis Missa; Aloysius Djalo; Yuliana A. Letok (Program Studi Pendidikan Biologi, 2025)
This study aims to analyze the teaching style of science teachers in relation to the learning motivation and activity of Grade VII D students at SMP Katolik Adisucipto Penfui, East Nusa Tenggara. The research method used is descriptive quantitative, with purposive sampling technique. The instrument used is a Likert scale questionnaire. This study focuses on three main variables: the teaching style of science teachers, learning motivation (interest, attention, willingness, and learning goals), and learning activity (participation, activeness in discussion, and task completion). The results show that the science teacher’s teaching style is generally rated very positively by the students. The teacher is considered capable of explaining the material clearly, using a variety of learning media, and creating positive interaction during the learning process. Furthermore, students’ learning motivation is categorized as high, as indicated by their enthusiasm for learning, desire to achieve, and efforts to complete tasks independently. Students' learning activity is also classified as active, marked by participation in discussions, asking questions, and taking notes effectively.